AN ECONOMIC ANALYSIS OF WATERSHED MANAGEMENT PROJECT - Bhuyan, B. (Journal of Soil and Water Conservation, 2022)
A study at micro-level in Nuapada district was undertaken to assess the economic impact of a watershed project on socio-economic conditions of the beneficiaries. The objectives set for the study were, to study the socio-economic conditions, impact of watershed management programme on land utilisation, productivity and cropping pattern, income and employment and extent of coordination among the participating functionaries. Purposively, the Bhaisadani watershed project in Boden block of Nuapada district was taken for detailed study. 26 hectares during Rabi with drastic reduction off allow land from 27 ha. to 2 ha. Productivity of crops, like rice, black gram, greengram, maize and mustard had increased with introduction of groundnut and vegetables. On livestock sector the project had significant impact on ’bullock and human labour utilisation. Human labour employment had increased by 98.30 per cent as against 226.30 per cent of bullock labour employment. The post project period indicated that 42.68 per cent of total income was contributed by agriculture, followed by 28.41 per cent from off farm resources. There was over all 256 per cent increase in income for all the households. The people’s participation was significant For effective functioning of the project, appropriate training, input delivery system and market mechanism need to be developed.